1974
DOI: 10.1161/01.cir.50.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Valvular Surgery on Antibody to the Group A Streptococcal Carbohydrate

Abstract: Because previous studies revealed that high levels of antibody to the group A streptococcal carbohydrate (A-antibody) persist in the serum of patients with chronic rheumatic valvular disease, the effect of valvular surgery on the level of this antibody was examined in the present study. Streptococcal antibody titers (ASO, anti-DNAse B, and A-antibody) were determined on 73 patients admitted for cardiac surgery: 36 with chronic rheumatic valvular disease and 37 with nonrheumatic cardiac or coronary disease. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Dudding and Ayoub reported anti-group A carbohydrate antibodies persistently elevated in patients with valvulitis (9), and surgical removal of inflamed valves resulted in a significant decrease in levels of anti-group A carbohydrate antibodies present in serum (40). We demonstrated previously that murine anti-streptococcal antibodies recognized valvular endothelium (41).…”
mentioning
confidence: 82%
“…Dudding and Ayoub reported anti-group A carbohydrate antibodies persistently elevated in patients with valvulitis (9), and surgical removal of inflamed valves resulted in a significant decrease in levels of anti-group A carbohydrate antibodies present in serum (40). We demonstrated previously that murine anti-streptococcal antibodies recognized valvular endothelium (41).…”
mentioning
confidence: 82%
“…Among the cross-reactive antibodies, CHO-Ab is of special interest because, in addition to cross-reactivity with the structural glycoproteins of the human cardiac valves [9,10], it has been reported to persist after an ARF attack only in patients who developed RHD [11][12][13]. The difference, however, could not be confirmed in a large series of patients studied with the agar diffusion precipitation technique [29] rather than the radioimmunoassay.…”
Section: Discussionmentioning
confidence: 99%
“…These included: cross-reactions between the streptococcal cell membrane and the human heart sarcolemmal sheaths [4,5], streptococcal cell membrane and basal ganglia [6], streptococcal M protein and myosin [7], the hyaluronic acid of the streptococcal capsule and the human synovial tissue [8], and the group A specific polysaccharide and the glycopeptides of the heart valves [9,10]. The latter finding was strengthened by the work of other colleagues who reported that elevated levels of the group A specific polysaccharide antibody (CHO-Ab), in the presence of normal titers of antistreptolysin O (ASO) and anti DNA se B, was only maintained in patients with ARF who developed rheumatic heart disease (RHD) [11][12][13]. Acute rheumatic fever, RHD and acute poststreptococcal glomerulonephritis (AGN) are still common in Arab countries [14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Group A carbohydrates have also been shown to trigger autoantibodies [32]. Antigroup A carbohydrate antibodies correlated with need for valve replacement and decreased following surgical removal of the diseased valve [33,34].…”
Section: Pathogenesis: Autoimmunitymentioning
confidence: 99%